AtERO1 and AtERO2 Exhibit Differences in Catalyzing Oxidative Protein Folding in the Endoplasmic Reticulum. Issue 4 (28th May 2019) - Fan, Fenggui; Zhang, Yini; Huang, Guozhong; Zhang, Qiao; Wang, Chih-chen; Wang, Lei; Lu, Dongping
Abstract : Both AtERO1 and AtERO2 play essential roles in oxidative protein folding in the endoplasmic reticulum, but AtERO1 may serve as the primary sulfhydryl oxidase relative to AtERO2 Abstract: Disulfide bonds are essential for the folding of the eukaryotic secretory and membrane proteins in the endoplasmic reticulum (ER), and ER oxidoreductin-1 (Ero1) and its homologs are the major disulfide donors that supply oxidizing equivalents in the ER. Although Ero1 homologs in yeast ( Saccharomyces cerevisiae ) and mammals have been extensively studied, the mechanisms of plant Ero1 functions are far less understood. Here, we found that both Arabidopsis ( Arabidopsis thaliana ) ERO1 and its homolog AtERO2 are required for oxidative protein folding in the ER. The outer active site, the inner active site, and a long-range noncatalytic disulfide bond are required for AtERO1's function. Interestingly, AtERO1 and AtERO2 also exhibit significant differences. The ero1 plants are more sensitive to reductive stress than the ero2 plants. In vivo, both AtERO1 and AtERO2 have two distinct oxidized isoforms (Ox1 and Ox2), which are determined by the formation or breakage of the putative regulatory disulfide. AtERO1 is mainly present in the Ox1 redox state, while more AtERO2 exists in the Ox2 state. Furthermore, AtERO1 showed much stronger oxidative protein-folding activity than AtERO2 in vitro. Taken together, both AtERO1 and AtERO2 are required to regulate efficient and faithful oxidative protein folding in the ER, but AtERO1 may serves as the primary sulfhydryl oxidase relative to AtERO2.